Behavioral issues in change - Burnes, Bernard (Henry Stewart Talks, 2009)
Reactions to change, The implications for employee involvement, Understanding and managing change, A planned approach, Workgroup behavior, Action research, Three step model, Planned change, Emergent change, Creating a climate for change, Changing managerial behavior, The emergent approach, Contingency approach, The scope for choice, The role of managers
Archived at 2025/05/28